Optimalisasi Media Podcast dalam Pembelajaran Jarak Jauh untuk Ekstrakurikuler Kelompok Ilmiah Remaja di SMA Negeri 1 Tambangan Kabupaten Mandailing Natal - Ali, Muttaqin Kholis; Ali, Al Muhtadibillah; Hasanah, Arrahmil (HORIZON: Indonesian Journal of Multidisciplinary, 2024)
This research aims to optimize the use of podcast media in distance learning for extracurricular Youth Scientific Groups (KIR) at SMA Negeri 1 Tambangan, Mandailing Natal Regency. This research uses the Research and Development (R&D) method with the ADDIE model. The subject of this study involved 35 KIR member students. Podcast development goes through the stages of analysis, design, development, implementation, and evaluation. The results showed that the developed podcast received a "Very Good" rating from material experts (score 3.55) and media experts (score 3.65). The student response was also very positive with an average score of 3.75. The implementation of podcast media showed a significant increase in student understanding, as evidenced by the N-Gain Score analysis. Media Podcast proves to be a flexible, accessible, and engaging learning medium for students in the context of distance learning. This research contributes to the development of distance learning methods for extracurricular activities, with podcast media as an effective solution in overcoming learning challenges during the pandemic